Faktor-Faktor Yang Mempengaruhi Minat Beli Konsumen Pada Plat Form Shopee - Regita Kusuma Dewi; Dedi Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze the factors that influence consumer buying interest on the Shopee platform. Into day's digital era,e-commerceplat forms like Shopee have be come one of the mainplaces for consumers to make purchases online. Therefore, a deep understanding of the factors thatinfluence consumer buying interest on this platform is essential for business success and an effective marketing strategy. This studyu sesa survey research method using aquestion naireasadata collection instrument. There search sample consistsof consumer swhoactive lyuse the Shopee plat form. The collected data were analyzed using regression analysis to identify the factors tha tinfluence consumer buy inginterest. The results of the study show that there are several factors that have a significant effect onconsumer buying interest on the Shopee platform. These factors include consumer confidence in theplatform, product quality, ease of use, and competitive price offerings. Consumer trust in the Shopeeplatform is the most important factor influencing their buying interest. Based on the results anddiscussion, it can be concluded that the factors that influence consumer buying interest on the Shopeeplatform include trust, product quality, ease of use, and competitive price offers. The implication ofthis research is the importance of building consumer trust through transaction security, providing quality products, ensuring an intuitive user interface, and offering competitive prices to increase consumer buying intereston the Shopee plat form.Â